Measures for economic development and poverty reduction in the republic of Uzbekistan - Tojiboyeva Nargiza Jumaboyevna (International Journal on Orange Technologies, 2021)
This article discusses the concept of economics and economic development, and provides detailed information about economic development and its main factors. The article also highlights the problems of economic development and the elimination of problems related to poverty reduction in our country